CD38 ligation induces tyrosine phosphorylation of Bruton tyrosine kinase and enhanced expression of interleukin 5-receptor alpha chain: synergistic effects with interleukin 5. - Kikuchi, Y (1995)
Mouse CD38 has been implicated in the regulation of both B-cell proliferation and protection of B cells from irradiation-induced apoptosis. CD38 ligation on B cells by CS/2, an anti-mouse CD38 monoclonal antibody, induced proliferation, IgM secretion, and tyrosine phosphorylation of Bruton tyrosine kinase in B cells from wild-type mice. B cells from X chromosome-linked immunodeficient mice did not respond at all to anti-CD38 antibody, although CD38 expression on these B cells was comparable to that on wild-type B cells. We infer from these results that Bruton tyrosine kinase activation is involved in B-cell triggering after cross-linkage of CD38. Analysis of the synergistic effects of various cytokines with CD38 ligation on B-cell activation revealed that interleukin 5 (IL-5) showed the most potent effect on B-cell proliferation, Blimp1 gene expression, and IgM production. These synergistic effects were not seen with B cells from X chromosome-linked immunodeficient mice. Flow cytometry analysis revealed that CD38 ligation increased surface expression of the IL-5-receptor alpha chain on B cells. These data indicate that CD38 ligation increases IL-5 receptor alpha expression and synergizes with IL-5 to enhance Blimp1 expression and IgM synthesis.